Natural wealth and political regime : the resource curse - Frolov, Alexander (2023)
This bachelor's thesis looks at the potential relationship between the level of democracy in a country and the dependence on natural resources as a form of revenue for the government. The aim of the thesis is to test the hypothesis that increased resource dependence decreases the level of democracy in a country. In line with the Resource Curse thesis. The hypothesis is tested using pooling OLS on a sample of 125 countries, which is analyzed both as a large panel data sample and individually according to the continent of the countries origin. A negative correlation was found which supports the hypothesis of the thesis in 3 out of the 8 tested models. But, also a positive correlation was found in one of the models which challenges standard Resource Curse theory. The main contribution of the thesis are the empirical findings which support the existence of the resource curse, and validate the hypothesis of the thesis on each order of magnitude analyzed.